(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The present investigation was taken up to prepare and evaluate drug free polymeric patches using different polymers and to study the effect of different plasticizers on physicochemical properties of the patches to explore their feasibility for transdermal application. Polyethylene glycol (PEG 400), Dibutylphthalate (DBP) and Propylene glycol (PG) were used as plasticizers at a concentration of 40 % w/w of dry polymer weight. Drug free polymeric patches were prepared by the casting method on mercury surface and evaluated for weight variation, thickness, flatness, tensile strength, folding endurance, surface pH, hardness, swellability, water vapour transmission rate and skin irritation studies. The mercury substrate method was found to give thin uniform patches. The weight and thickness of the patches was found to be uniform. Tensile strength and folding endurance of the patches prepared with DBP as plasticizer was high compared to patches plasticized with PG and PEG. All the formulations show 100 % flatness. HPMC K4M: PVP patches plasticized with PEG 400 showed higher swellability and water vapour transmission rates. The patches were found to be free of any skin irritation. Based on the above observations, it can be reasonably concluded that plasticizers have a significant influence on the mechanical properties of the transdermal patches.